THE DEVELOPMENT OF LANGUAGE POLICY IN INDONESIA - Rahmi Rahmi (Universitas Islam Negeri Banda Aceh, 2015)
Indonesia has successfully implemented language policy by choosing Malay language as its national language which enables to unite ethnics from a variety of vernaculars’ background. However, Indonesia is not considered successful enough in preserving indigenous languages and promoting English as a crucial international language. In comparison with Indonesia, Malaysia and the Philippines faced some challenges when applying a language of majority as national language. Yet, both countries have more focuses to develop English in domestic level for global purposes. There are some sociolinguistic challenges for Indonesian policy makers in terms of local, national and international languages.